1993
DOI: 10.1002/ijc.2910540504
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation and oxidative‐DNA damage repair activity in blood leukocytes of smokers and non‐smokers

Abstract: The levels of 3 DNA repair enzymes involved in alkylation and oxidative DNA damage repair in human peripheral blood leukocytes were measured in 20 smokers and 17 non-smokers. No differences in O6-alkylguanine-DNA-alkyltransferase (AGT) activity were found between the 2 groups and the AGT distribution within the population appeared to be unimodal. In contrast, the mean activities of both the methylpurine (MeP)- and the 2-6-diamino-4-hydroxy-5N formamidopyrimidine (FaPy)-DNA glycosylases were higher in the smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Transcriptional profiling studies of S. cerevisiae have demonstrated that alkylation damage induces the transcription of hundreds of genes corresponding to proteins associated with DNA repair, cell-cycle checkpoints, amino acid metabolism and protein degradation (7)(8)(9)(10)(11). Protein degradation has been observed previously for components of the DNA damage response (12,13) and, in theory, can work to optimize essential enzyme activity. In addition, protein degradation is used to remove damaged or unfolded proteins.…”
Section: Introductionmentioning
confidence: 85%
“…Transcriptional profiling studies of S. cerevisiae have demonstrated that alkylation damage induces the transcription of hundreds of genes corresponding to proteins associated with DNA repair, cell-cycle checkpoints, amino acid metabolism and protein degradation (7)(8)(9)(10)(11). Protein degradation has been observed previously for components of the DNA damage response (12,13) and, in theory, can work to optimize essential enzyme activity. In addition, protein degradation is used to remove damaged or unfolded proteins.…”
Section: Introductionmentioning
confidence: 85%
“…In humans, enzymatic activities for the repair of oxidized DNA can vary up to 100‐fold (45), and the levels of 8‐oxo‐dG in lymphocytes vary sixfold in the population (46), suggesting that there may be subsets of the population that are at risk for increased levels of 8‐oxo‐dG. We have demonstrated herein that it is possible to regulate the endogenous level of 8‐oxo‐dG in vivo , in binary transgenic actin‐tTA:tetO‐fpg mice overexpressing the bacterial fpg DNA repair enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found the expected higher levels of 8-oxodG and other oxidative bases or strand breaks in leukocyte DNA from smokers as compared with nonsmokers, although this is far from consistent (10,28,47,52). Inconsistencies may be due to possible induction of OGG1 activity by smoking (28,34). Exposure to ambient air particles and benzene has consistently been associated with high levels of 8-oxodG in lymphocytes (2,81,82,92).…”
Section: Factors Affecting Biomarkers Of Oxidative Dna Damage In Humansmentioning
confidence: 98%
“…The capacity for nicking of labeled oligonucleotides with, for example, oxidized bases or ethenoadducts by extracts of cells or tissues is measured relatively easily (34,84). Similarly, cell extracts can be applied on nucleoids with a defined level of, for example, 8-oxodG induced by a photosensitizer and nicking assessed by the comet assay (16).…”
Section: Biomarkers Of Dna Repair Capacitymentioning
confidence: 99%